The Effect of Divorced Parents’ Parenting Patterns and Children’s Stress Levels on Resilience in Surabaya City - yessi pramudita; Arbi Osta Samsul Sarif Hidayatullah (Journal of Art and Creativity in Early Childhood Education, 2025)
This study investigates the influence of divorced parents’ parenting styles and children’s stress levels on resilience among early childhood populations in Surabaya City. Increasing rates of divorce in Indonesia raise concerns regarding the psychological well-being of children, particularly related to parenting practices and stress, which may affect their ability to develop resilience. A quantitative survey method was applied with purposive sampling to select children aged 4–6 years from divorced families. Data were collected using closed-ended questionnaires developed based on standardized theoretical indicators. Inferential statistical analyses were employed, including multiple correlation to examine relationships between variables, multiple linear regression to determine the contribution of each independent variable to resilience, and path analysis to explore direct and indirect effects. The findings reveal a significant relationship between parenting style and resilience, as well as between stress level and resilience. Furthermore, both independent variables simultaneously contributed significantly to resilience outcomes. Path analysis results indicate that stress serves as a mediating factor linking parenting style to resilience, suggesting that ineffective or inconsistent parenting increases stress, which subsequently reduces resilience. The study concludes that divorced parents’ parenting practices and children’s stress levels jointly influence resilience. Therefore, supportive parenting and interventions to reduce childhood stress are essential for strengthening resilience among children in divorce contexts.